COMBUSTION OPTIMIZATION AND CONTROL SYSTEM BASED ON MEASUREMENT OF FURNACE TEMPERATURE FIELD VIA SOUND WAVE AND CONTROL METHOD THEREFOR - DONG, XINGUANG; YANG, XINGSEN; HAO, WEIDONG; LIU, FUGUO; HU, ZHIHONG (2014)
A combustion optimization and control system based on measurement of furnace temperature field via sound wave and a control method therefor, comprising a data collecting device (10), a data processing device (12), an operation mode selecting module (11), an execution instruction output module (13), wherein the data processing device (12) is encapsulated with a coal quality processing module (1), a soot-blowing mode processing module (2), an air distribution mode processing module (3) for auxiliary air flow, a furnace temperature field data processing module (4), a furnace temperature field homogenising module (5), a boiler auxiliary operation mode processing module (6), a module (7) for processing the boiler coal mill commissioning manner, the execution instruction output module (13) comprising an oxygen amount adjustment module (8) and a furnace temperature adjustment module (9). The system constructs a combustion automatic adjustment system which improves the efficiency of combustion of the boiler. L'invent